The Borders of Islam : Exploring Huntington's Faultlines, from Al-Andalus to the Virtual Ummah - Edited by Hansen, Stig Jarle ; Mesøy, Atle and Kardas, Tuncay (New Delhi Foundation Books, 2009)
Offers a set of essays that examines the border zones of Islamic civilisation, be they geographical, cultural or virtual. This book explores the local dynamics in these zones to test whether or not they support or contradict professor Samuel P Huntingdon's thesis of an emerging global confrontation between Islamic civilisation and its neighbours
Include Notes and Index
Keywords: Interfaith relations -- Islamic civilization -- East and West